A cousin's prayer - Brunstetter, Wanda E. (Uhrichsville, OH : Barbour Pub., 2009)
Traumatized after surviving an automobile accident in which her boyfriend was killed, Katie Miller struggles to find her way out of depression, while Freeman Bontrager tries to gain Katie's trust in hopes of winning her heart.
"All scripture is taken from the King James Version of the Bible"--T.p. verso.
"All German-Dutch words are taken from the Revised Pennsylvania Dutch Dictionary found in Lancaster County, Pennsylvania"--T.p. verso.
Includes discussion questions.
Keywords: Amish -- Indiana -- Fiction; Amish -- Fiction; Traffic accidents -- Fiction; Indiana -- Fiction; Love stories; Christian fiction